Challenges and controversies in childhood tuberculosis. Issue 10202 (14th September 2019) - Reuter, Anja; Hughes, Jennifer; Furin, Jennifer
Summary: Children bear a substantial burden of suffering when it comes to tuberculosis. Ironically, they are often left out of the scientific and public health advances that have led to important improvements in tuberculosis diagnosis, treatment, and prevention over the past decade. This Series paper describes some of the challenges and controversies in paediatric tuberculosis, including the epidemiology and treatment of tuberculosis in children. Two areas in which substantial challenges and controversies exist (ie, diagnosis and prevention) are explored in more detail. This Series paper also offers possible solutions for including children in all efforts to end tuberculosis, with a focus on ensuring that the proper financial and human resources are in place to best serve children exposed to, infected with, and sick from all forms of tuberculosis.